The Last of the Plainsmen - Grey, Zane, 1872-1939 (Salt Lake City, UT : Project Gutenberg, 2000)
"The Last of the Plainsmen" by Zane Grey is an adventure novel written during the early 20th century. The book chronicles the life and pursuits of a unique individual known as Buffalo Jones, who is dedicated to the capture and preservation of American bison. With a backdrop of the American West, the narrative captures the essence of exploration and the interaction between man and nature as it follows Buffalo Jones and his companions on their quest across the wilderness. The opening of the book introduces readers to Buffalo Jones, a passionate and rugged character dedicated to saving bison as civilization encroaches on their habitats. Set against the expansive and harsh landscape of the Arizona desert, the narrator describes a journey shared with Jones, illustrating his engaging and somewhat eccentric personality. Their expedition quickly conveys the struggles and beauty of the wilderness, as they endure elements like dry air, vast stretches between water sources, and encounters with Native Americans and wild animals. The opening reveals the bond between the narrator and Jones and sets the stage for a series of thrilling adventures focused on the preservation of wildlife in a rapidly changing world. (This is an automatically generated summary.)
Release date is 2000-02-01
Produced by Mary Starr. HTML version by Al Haines.
Keywords: Western stories; Biographical fiction; Pioneers -- Fiction; Jones, Charles Jesse, 1844-1919 -- Fiction